COVID-19 Pandemic and Dynamics of Worship Fatwas between States In Malaysia: A Preliminary Comparative Review (Lembaga Contrarius Indonesia, 2026)
The COVID-19 pandemic that struck globally has led to a sharp increase in mortality rates and significantly impacted various aspects of life in Malaysia. To curb the spread of the virus, the Malaysian government implemented the Movement Control Order (MCO), which altered many dimensions of daily living, including religious practices. This situation also influenced changes and variations in the fatwas issued by different fatwa institutions across Malaysia. This study examines the dynamics of change and divergence in fatwas related to acts of worship across Malaysian states during the pandemic, particularly regarding Friday and congregational prayers, row distancing in congregational prayers (saf), and the practice of face mask use. Employing a qualitative approach, the research draws on secondary data from official documents, literature reviews, and the official websites of religious authorities. The findings reveal that variations in fatwas across states were influenced by social and demographic factors, as well as differences in the administrative jurisdictions of religious institutions. These changes, however, were made in accordance with Islamic legal principles to uphold the maqāṣid al-sharī’ah, particularly the preservation of life. This aligns with key legal maxims such as lā ḍarar wa lā ḍirār and al-masyaqqah tajlibu al-taisīr. The study concludes that fatwa adaptations issued during the COVID-19 pandemic were prudent and reflect the flexibility and wisdom of Islamic law in addressing contemporary emergencies. Therefore, it is recommended that Malaysia’s experiences during the pandemic be systematically documented and analyzed as a foundation for developing comprehensive guidelines and frameworks for future fatwa and ijtihad responses to potential public health crises.